Evaluation of the Implementation of Healthy Food Provision for Early Childhood at Muslimat Nu Puton Kindergarten in Pekalongan - Amin, Moh. Hikam Istifaul; Wahyuningsih, Wahyuningsih; Fathonah, Siti; Sugeng, Bambang (Food Science and Culinary Education Journal, 2023)
Early Childhood Education in addition to providing educational services as well in the form of early childhood nutritional health services implemented through provision of a healthy and nutritionally balanced diet to help growth and support physical and spiritual development, as well as to help develop the potential for spiritual, intellectual, emotional and social intelligence in early childhood through the Provision of Healthy Food. The aims of this study were 1) to find out the mechanism for implementing healthy food at the Muslimat NU Puton Kindergarten in Pekalongan. 2) To find out the criteria for providing healthy food at the Muslimat NU Puton Kindergarten in Pekalongan. 3) To find out the extent of achievement in implementing healthy food at the Muslimat NU Puton Kindergarten in Pekalongan. The method used in this research is descriptive qualitative. Data collection techniques using interview techniques, observation, and documentation. The results showed that 1) The implementation of healthy food for young children in Muslimat Kindergarten NU Puton Pekalongan is given once a week which is held every Thursday at 10.00 WIB for lunch for children after carrying out learning and playing activities, the menu given every week is different Different, namely in the form of healthy snacks/snacks and main meals so that children don't get bored of receiving healthy food at school. 2) The criteria for providing healthy food to children at the Muslimat NU Puton Pekalongan Kindergarten have not been fully implemented in accordance with the existing criteria, the criteria that have not been implemented are that in the process of making food for cooks they have not used personal protective equipment (PPE) and the food ingredients used have not been fully using local ingredients. 3) The achievement of implementing healthy food at the Muslimat NU Puton Kindergarten in Pekalongan seen from the aspect of increasing children's development according to their age stages, increasing children's weight and height, as well as parental involvement in parenting activities can be said to be successful.